Optimization of extruder cooking conditions for the manufacture of fish feeds using response surface methodology - Irungu, F.G.; Mutungi, C.; Faraj, A.; Affognon, Hippolyte D.; Ekesi, S.; Nakimbugwe, D.; Fiaboe, K.K.M. (Wiley, 2019)
A composite blend consisting of sunflower cake, maize germ, wheat bran, fresh water shrimps and cassava flour was extruded using a single-screw extruder to produce expanded fish feed pellets. The effects of temperature (80–120 C), die diameter (2–4 mm), and feed pre-conditioning time (50–150 s; steam 400 kPa) on properties of the pellets (expansion ratio, bulk density, floatability, durability, water absorption, water solubility, water stability, and in-vitro protein digestibility) were investigated using response surface methodology. Regression equations describing the effect of each variable on the product responses were obtained. The pellets extruded using a factor combination of 120 C extruder barrel temperature, 2 mm die diameter, and 100 s of feed preconditioning time gave most desirable pellet floatability (100%), durability index (99%), expansion ratio (2.64), water absorption index (4.12), water solubility index (9.31), water stability (87%), bulk density (479 g/L), and in vitro protein digestibility (69.97%) with a composite desirability of 0.88. Practical applications Extrusion is a modern feed processing method whose use is fast gaining popularity among small feed processors in developing countries. However, extrusion is a process that involves many parameters that need to be optimized for desirable end properties. These findings guide fish feed manufacturers on the optimum conditions for single screw extruders for production of feeds with desirable properties especially for the fish types that are top feeders. In addition, the results offer important insights on how temperature, die diameter, and feed pre-conditioning, may be manipulated to influence properties of extruded aquafeed when using simple low-cost small-scale extruders.